ICASSP 2019 - 2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2019
DOI: 10.1109/icassp.2019.8682361
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel Time Encoding for Improved Reconstruction of Bandlimited Signals

Abstract: Traditional sampling involves encoding a signal through (time, value)-pairs. In contrast, time encoding machines (TEMs) characterize a signal by recording time points which depend on the integral of the signal over time. We study multi-channel TEMs where channels have shifted values for their integrators. We show that M channels can enable recovery of bandlimited signals with M times the bandwidth of that allowed in the single channel case. Moreover, our recovery algorithm is linear, even when the shift betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…We have thus shown that using M time encoding machines to encode a 2Ω-bandlimited signal x(t) allows a bandwidth Ω which is M times larger than in the single channel case, no matter how the shifts between the machines are configured, as long as they are all nonzero. As already stated, we had shown in [22] that the bandwidth could become M times larger, but only if the machines were configured in such a way that their integrators had equally spaced values. In other words, if we denote y i (t) to be the value of the integrator of machine i, then we required, ∀i = 1 · · · M − 1,…”
Section: Uniqueness Of M-channel Reconstruction Using Pocsmentioning
confidence: 67%
“…We have thus shown that using M time encoding machines to encode a 2Ω-bandlimited signal x(t) allows a bandwidth Ω which is M times larger than in the single channel case, no matter how the shifts between the machines are configured, as long as they are all nonzero. As already stated, we had shown in [22] that the bandwidth could become M times larger, but only if the machines were configured in such a way that their integrators had equally spaced values. In other words, if we denote y i (t) to be the value of the integrator of machine i, then we required, ∀i = 1 · · · M − 1,…”
Section: Uniqueness Of M-channel Reconstruction Using Pocsmentioning
confidence: 67%
“…Given these constraints on the signal we can also derive the minimum possible value of |D| by substituting x0 = −xmin and x i =0 = xmax into equation (11). This can then be used to determine the appropriate trigger mark, CT < |D| to generate a given number of samples within the interval [t0, t0 + t * ].…”
Section: Conditions For Guaranteed Spikingmentioning
confidence: 99%
“…[8,9]. Time encoding systems have been previously used for reconstructing signals in shift-invariant spaces [10][11][12][13][14][15], as well as FRI signals in [16][17][18][19] using exponential spline sampling kernels and in [20] using hyperbolic secant kernels.…”
Section: Introductionmentioning
confidence: 99%
“…First, we review time encoding machines (TEMs), which are the ideal event-based sensor [7,12]. The input-output relationship of an integrateand-fire TEM follow similar rules to that of nonuniform sampling [13,14], and thus results in interesting consequences when it comes to single-signal multi-channel time encoding [15,16].…”
Section: Introductionmentioning
confidence: 99%